Comparison between manual and automated methods for the isolation of mononuclear cells and mesenchymal stem cells using ficoll: efficacy and reproducibility - Moñivas, Ester; Aguayo, Concepción; de la Calle, Silvia; Martínez, Paula; Repollés, Nieves; Zurita, Mercedes (Frontiers in Cell and Developmental Biology, 2025)
Mesenchymal stem cells (MSCs), hold immense therapeutic promise in Advanced Therapy Medicinal Products (ATMPs) due to their multipotent nature, immunomodulatory properties, and anti-inflammatory effects. However, a significant challenge lies in obtaining sufficient quantities of MSCs for therapeutic applications, necessitating ex-vivo culture of Mononuclear Cells (MNCs) isolated from source tissues like bone marrow. This study compares the efficacy of MNC isolation using manual and automated methods, specifically evaluating the Sepax system, and investigates whether the isolation method impacts MSCs yield. Seventeen bone marrow samples were processed using both methods, with subsequent analysis of MNC and colony-forming unit (CFU) counts, MSCs differentiation potential, and phenotypic characterization. While the Sepax system demonstrated slightly higher MNC yields, no significant differences were observed in CFU formation or MSCs characteristics compared to manual isolation. These findings underscore the importance of critically evaluating isolation methods to ensure both efficiency and quality in therapeutic applications.